Epidemiology of diabetes mellitus and microvascular complications - Oksana Vladimirovna Maslova; Yury Ivanovich Suntsov (Сахарный диабет, 2011)
The present work is devoted studying of epidemiological situation of diabetes mellitus (DM). The data on prevalence and incidence of DM and itsmicrovascular complications among adult population in the different countries of the world is presented. The analysis of numerous researches allowsto speak about high prevalence of this disease all over the world and to allocate a number of the most significant risk factors of development andprogressing of diabetic complications.